(untitled) (Law Research Review Quarterly, 2025)
This study examines the implementation of local retribution collection at the Sport Center Manunggal Jati in Semarang City from the perspective of positive law and the principles of good governance. The main issue addressed is the extent to which the regulation and implementation of user service retribution in this sector align with the general principles of good administration. The research adopts a normative juridical method with a descriptive-analytical approach. Data were obtained through literature studies on statutory regulations, local government documents, and previous research findings. The results reveal that the legal framework for retribution collection is well-established, both at the national and regional levels, including Law Number 1 of 2022, Government Regulation Number 35 of 2023, Semarang Regional Regulation Number 7 of 2018, and Mayor Regulation Number 6 of 2020. However, implementation still faces challenges such as limited public outreach, suboptimal administrative systems, and insufficient supervision. Nevertheless, the retribution collection at Sport Center Manunggal Jati reflects the principles of legal certainty, utility, impartiality, non-abuse of power, and public interest. The study concludes that strengthening management systems, conducting regular regulatory evaluations, and applying digital technology are essential to improve the efficiency and accountability of retribution administration.